MONITORING PERTUMBUHAN KELAPA SAWIT FASE BELUM MENGHASILKAN BERBASIS PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFI DI PTPN IV REGIONAL I - HUTAURUK, JEREMIA; Hariyadi; Suprihatin (Institut Teknologi Sawit Indonesia, 2024)
PT Perkebunan Nusantara IV Regional I is a BUMN that manages palm oil and rubber commodities. One of the factors that influences productivity is management during the immature plant phase. The aim of using GIS and Remote Sensing technology is to find out how to monitor oil palm growth in TBM phase effectively. This research was conducted in North Sumaera at TBM Sawit PTPN IV Regional I in a total of 27 plantations with an area of ​​15,286.39 ha (9.78% of the company area). The time of this research is January to September 2024. This research uses several methods, namely remote sensing methods, orthorectification, preparing a TBM geodatabase, digitizing maintenance, identifying plant health, compiling TBM tabular data and making layouts. First results of monitoring are aerial photos of oil palm TBMs, ortho photo results, spatial data on condition of normal, dead, non-valued/dwarf trees and inset trees, raster analysis of nut growth, spatial data on maintenance conditions, identification of plant diseases in TBM 1 using a multispectral camera with 82% accuracy and correlation of digital data and survey field measurements for the growth parameters of rachis length, stem diameter and number of fronds, so that a correlation between digital crown circumference and stem diameter of 1:0.124 was obtained, with rachis length 1:0.164, and the number of fronds 1:0.022. From this research it can be concluded that use of remote sensing technology and GIS can monitor the growth of palm oil TBM at PTPN IV Regional I